Students Perception about Counselors Communication Skills: The Differences Based on Gender and Grades in Junior High Schools - Awalya, Awalya; Suharso, Suharso; Rifani, Endang; Syifa, Layyinatus; Saputra, Fikie; Susilawati, Susilawati; Anggraini, Weni (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2020)
Individual counseling services which are not in line with the procedures and goals may lead to students’ negative perceptions. To know this, there are several indicators to be examined whether the services have been in line with the procedures or not, such as listening skills, techniques used, goal setting, and others. Regarding these preliminary findings, this study aimed at describing students’ perceptions of individual counseling services provided by counselors in Semarang, Indonesia and its differences in terms of counselor communication skills based on genders and grades. Survey method with cross-sectional technique (n=709) was employed to investigate this issue. To determine students’ perception of the implementation of individual counseling by the counselor, the authors used MANOVA and multidimensional descriptive analysis. The findings showed that according to gender, male students had lower perceptions of the individual counseling given by counselors than female students. Further, differences in perceptions based on grades are also discussed in this article.